1999
DOI: 10.1007/s004649901189
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal immunity and pneumoperitoneum

Abstract: In this animal model, CO(2) pneumoperitoneum impaired cell-mediated intraperitoneal immunity significantly more than He pneumoperitoneum and controls on day 3. Also on day 3, laparotomy caused impairment of intraperitoneal immunity when compared to controls. Finally, intraperitoneal immunosuppression resolved by day 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…Thus it has been reported that carbon dioxide suppresses the function of peritoneal macrophages while helium insufflation did not have any influence on cell function [6]. Furthermore Puttick et al [7]analyzed tumor cell lyses by macrophages after gas incubation with either 100% carbon dioxide or 100% helium and found a significant decrease in cell lyses in the carbon dioxide group while helium had no negative effects on cell lyses.…”
Section: Experimental Studies Investigating the Influence Of The Pneumentioning
confidence: 99%
“…Thus it has been reported that carbon dioxide suppresses the function of peritoneal macrophages while helium insufflation did not have any influence on cell function [6]. Furthermore Puttick et al [7]analyzed tumor cell lyses by macrophages after gas incubation with either 100% carbon dioxide or 100% helium and found a significant decrease in cell lyses in the carbon dioxide group while helium had no negative effects on cell lyses.…”
Section: Experimental Studies Investigating the Influence Of The Pneumentioning
confidence: 99%
“…These findings contribute to explain the reduction of cytokine release when animals and patients are operated under effect of CO 2 pneumoperitoneum. Whereas these effects might be considered beneficial from the standpoint of inflammation following elective surgery, one experimental study suggests that CO 2 induced immunossuppression might be deleterious in the setting of infection 13 . The clinical significance of these findings remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, CO 2 blocked superoxide release from activated polimorphonuclear leukocytes and significantly reduced the secretion of IL-1 from human peritoneal macrophages 12 . Whereas these effects might be considered beneficial from the standpoint of inflammation following elective surgery, experimental evidence suggests that the CO 2 induced immunossuppression might be deleterious in the setting of infection 13 . This may have an adverse effect on clinical outcome when compared with open procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal macrophages function as the immune system's first line of defense in the abdominal cavity. A fair number of small animal studies that assessed peritoneal macrophage function after carbon dioxide pneumoperitoneum have reported diminished macrophage cytokine release and impaired ability of the macrophages to clear intraperitoneal bacterial loads [25][26][27]. Other animal studies, however, have reported conflicting results.…”
Section: F Peritoneal Macrophagesmentioning
confidence: 99%